EFFECTS OF PSYCHOSOCIAL FACTORS AND TRUST IN SCIENCE ON INTENTION TO SEEK INFORMATION AMONG PEOPLE ABOUT NONCOMMUNICABLE DISEASES - S Rouli Manalu; Yohanes Thianika Budiarsa; Kholidil Amin; Thaiane Oliveira (Universitas Airlangga, 2026)
Introduction: Noncommunicable diseases (NCDs) account for 74% deaths globally and 69% of deaths in Indonesia. A determining factor is one’s lifestyle of often neglecting health, emphasizing the need for access to reliable health information. Aims: This study, using the extended theory of planned behavior framework, was conducted to explore how psychosocial factors and trust in science influence Indonesian’s intention to seek information about NCDs. Methods: This cross-sectional study enrolled Indonesia residents aged >18 years. Using a nonprobability sampling method, a sample size of 809 respondents was recruited. Data were analyzed using structural equation modeling to assess the relationship within the measurement and structural models. Results: Attitude, subjective norms, and perceived behavioral control were psychosocial factors identified to affect the intention to seek health information. Trust in science was another predictor of the intention. Conclusion: Theoretically, these findings offer valuable insights into enhancing the theory of planned behavior framework by incorporating factors, such as trust in science. Practically, this research provides recommendations for health communicators and policymakers to increasingly engage the Indonesian population on NCDs through community empowerment and health promotion by collaborating with community health centers and higher education sectors.